Comparison of new point-of-care troponin assay with high sensitivity troponin in diagnosing myocardial infarction - Aldous, S.; Mark Richards, A.; George, P.; Cullen, L.; Parsonage, W.; Flaws, D.; Florkowski, C.; Troughton, R.; O'Sullivan, J.; Reid, Christopher; Bannister, L.; Than, M. (Elsevier Ireland Ltd, 2014)
Objectives: The aim of this study is to compare a new improved point of care cardiac troponin assay (new POC-cTnI) with 1. its predecessor (old POC-cTnI) and 2. a high sensitivity assay (hs-cTnI) for the diagnosis of acute myocardial infarction (AMI) and for major adverse cardiac events (MACE) by 30 days. Methods: This is a single centre observational study, set in Christchurch Hospital, New Zealand. Patients presenting to the emergency department with non-traumatic chest pain underwent blood sampling at 0 h and 2 h post presentation for analysis with the 3 cTnI assays for the outcome of AMI and for analysis using an accelerated diagnostic protocol (ADP-normal 2 h troponins, normal electrocardiograms and Thrombolysis In Myocardial Infarction (TIMI) score of 0 or ≤ 1) for 30 day MACE. Results: Of 962 patients, 220 (22.9%) had AMI. Old POC-cTnI was least sensitive at 70.0% (65.4–73.9%) by 2 h (p < 0.001). New POC-cTnI, sensitivity 93.6% (89.9–96.2%) had similar sensitivity to hs-cTnI, sensitivity 95.0% (91.5–97.3%) (p = 0.508). There were 231 (24.0%) patients with 30 day MACE. When used as part of the ADP, all assays had 100% (98.0–100%) sensitivity using TIMI = 0. Sensitivities of new POC-cTnI ADP, 98.3% (95.4–99.4%), old POC-cTnI, 96.5% (93.2–98.4%) and hs-cTnI, 98.7% (96.0–99.7%) were similar (p = 0.063–0.375) using TIMI ≤ 1. Conclusions: A new POC-cTnI has improved sensitivity for AMI and MACE compared with its predecessor and comparable sensitivity to a high sensitivity assay. Now that sensitivities of the POC assay are improved, the new assay may be a useful alternative to central laboratory assays when rapid turn-around times are not possible.